The Historical Transformation and Cultural Diffusion of the Ocarina: A Systematic Literature Review on Its Global Evolution and Introduction to Indonesia - Alfi Rifai Wahab; Agus Cahyono; Muh Fakhrihun Naam (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
: This article presents a literature review on the historical transformation and cultural diffusion of the ocarina, with a particular focus on its global evolution and its emergence in Indonesia. As a member of the vessel-flute family, the ocarina has undergone a long historical trajectory, evolving from a prehistoric artifact into a modern musical instrument with both educational and artistic functions. The literature indicates that the modern form of the ocarina was developed in Italy by Giuseppe Donati in the nineteenth century and subsequently disseminated to various regions of the world through trade routes, music education, and popular culture. In Indonesia, the ocarina has begun to attract attention as an alternative musical instrument in primary education and as part of creative clay-based craftsmanship. This study underscores the importance of cross-cultural perspectives in understanding the evolution of musical instruments and recommends further research focusing on local practices, craft production, and pedagogical integration within educational institutions.   Keywords: ocarina, vessel flute, music history, cultural diffusion, music education, Indonesia